The Influence of GST on the financial performance of women entrepreneurs: A Review (Journal of Advances and Scholarly Researches in Allied Education, 2023)
The Goods and Services Tax (GST) has significantly impacted various sectors of the economy, including women entrepreneurship. This review explores the influence of GST on the financial performance of women entrepreneurs, emphasizing its implications for business operations, profitability, and growth. The study synthesizes findings from secondary data sources, including academic articles, government reports, and industry analyses, to understand the broader impacts of GST on women-led businesses. By examining key aspects such as tax compliance, cost structures, and financial management practices, this review aims to provide a comprehensive overview of how GST policies have shaped the financial landscape for women entrepreneurs. The findings suggest that while GST has introduced opportunities for greater formalization and tax credit benefits, it has also posed challenges related to compliance and increased operational costs.